PEDOT Composite with Ionic Liquid and Its Application to Deformable Electrochemical Transistors - Sangkyu Lee; Jaepyo Jang; Sungjun Lee; Daekwang Jung; Mikyung Shin; Donghee Son (Gels, 2022)
Organic electrochemical transistors (OECTs) have become popular due to their advantages of a lower operating voltage and higher transconductance compared with conventional silicon transistors. However, current OECT platform-based skin-inspired electronics applications are limited due to the lack of stretchability in poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS). Some meaningful structural design strategies to resolve this limitation, including rendering OECT to make it more stretchable, have been reported. However, these strategies require complicated fabrication processes and face challenges due to the low areal density of active devices because wavy interconnect parts account for a large area. Nevertheless, there have been only a few reports of fully deformable OECT having skin-like mechanical properties and deformability. In this study, we fabricated stretchable and conductivity-enhanced channel materials using a spray-coating method after a composite solution preparation by blending PEDOT:PSS with several ionic liquids. Among these, the PEDOT composite prepared using 1-butyl-3-methylimidazolium octyl sulfate exhibited a better maximum transconductance value (~0.3 mS) than the other ion composites. When this material was used for our deformable OECT platform using stretchable Au nanomembrane electrodes on an elastomer substrate and an encapsulation layer, our d-ECT showed a barely degraded resistance value between the source and drain during 1000 cycles of a 30% repeated strain. We expect that our d-ECT device will serve as a step toward the development of more precise and accurate biomedical healthcare monitoring systems.